Theories as a Constitutive Feature of Scientificity and Their Place in Czech Historiography - Horský, Jan (Dějiny – teorie – kritika, 2011)
This is a report about the Xth Congress of Czech Historians, which took place on September 14–16, 2011 in Ostrava. It aims to outline the structure of discussions on the position of theories in Czech historiography in the past ten years. In the area of ‘theories about historical science’, it focuses on the contributions of Miloš Havelka (the notion of a ‘symbolic centre’, identification of three basic paradigms of the philosophy of history) and on the concepts proposed by Zdeněk Vašíček (duality of ‘story’ and ‘picture’, ‘archeologisation of history’). With regard to the place of theory in historical sciences, the author highlights studies (Daniela Tinková, Lucie Storchová, Veronika Čapská) that focus on comparing a general theoretical concept with empirical material. And last but not least, the article tries to evaluate the position of theoretical thinking in Czech ‘historiographical environment’ in the broadest sense, concluding that it does not seem to be particularly prominent.